Service delivery interventions to improve maternal and newborn health in low- and middle-income countries: scoping review of quality improvement, implementation research and health system strengthening approaches - Solange Mianda; Olamide Todowede; Helen Schneider (BMC, 2023)
Abstract Introduction This review explores the characteristics of service delivery-related interventions to improve maternal and newborn health (MNH) in low-and middle-income countries (LMICs) over the last two decades, comparing three common framings of these interventions, namely, quality improvement (QI), implementation science/research (IS/IR), and health system strengthening (HSS). Methods The review followed the staged scoping review methodology proposed by Levac et al. (2010). We developed and piloted a systematic search strategy, limited to English language peer-reviewed articles published on LMICs between 2000 and March 2022. Analysis was conducted in two-quantitative and qualitative-phases. In the quantitative phase, we counted the year of publication, country(-ies) of origin, and the presence of the terms 'quality improvement', 'health system strengthening' or 'implementation science'/ 'implementation research' in titles, abstracts and key words. From this analysis, a subset of papers referred to as 'archetypes' (terms appearing in two or more of titles, abstract and key words) was analysed qualitatively, to draw out key concepts/theories and underlying mechanisms of change associated with each approach. Results The searches from different databases resulted in a total of 3,323 hits. After removal of duplicates and screening, a total of 231 relevant articles remained for data extraction. These were distributed across the globe; more than half (n = 134) were published since 2017. Fifty-five (55) articles representing archetypes of the approach (30 QI, 16 IS/IR, 9 HSS) were analysed qualitatively. As anticipated, we identified distinct patterns in each approach. QI archetypes tended towards defined process interventions (most typically, plan-do-study-act cycles); IS/IR archetypes reported a wide variety of interventions, but had in common evaluation methodologies and explanatory theories; and HSS archetypes adopted systemic perspectives. Despite their distinctiveness, there was also overlap and fluidity between approaches, with papers often referencing more than one approach. Recognising the complexity of improving MNH services, there was an increased orientation towards participatory, context-specific designs in all three approaches. Conclusions Programmes to improve MNH outcomes will benefit from a better appreciation of the distinctiveness and relatedness of different approaches to service delivery strengthening, how these have evolved and how they can be combined.